Towards a mid-range theory of method selection for innovation pre-project activities - Herzberg, Torsten (Cranfield University, 2006)
There is a large variety of approaches that describe the pre-project innovation phase as the cradle of successful innovation activities, and thus as an important factor to reach the objective of organisational growth and competitive advantage. However, theoretical contributions to date mainly address this phase either from a strategic or from an organisational perspective. On a conceptual level, the developed methods are either specific to an organisational situation, or too general to be applied in a specific problem situation. In consequence, there is a missing link between strategy, organisation and concept development in theory about the early stage innovation activities. Thus, the innovation pre-project phase is not researched in an holistic way, which prevents a structured accumulation of knowledge in the research field. In this thesis, this gap is being bridged by developing a mid-range theory about the appropriate selection of methods in different, generic organisational situations. The theoretical framework consists of four theoretically derived situations and a set of generic activities that are conducted in pre-project innovation phases. The framework builds upon the research fields of decision-making and problem-solving theory, strategy development, and the contingency view. By combining these perspectives, the strategic problem of generating profit can be solved by the two second order problems of organising and conceiving new products or services. Profit can be generated by solving customers' problems, and this can be pursued by organising this process together with external collaboration partners in a value chain or network. In consequence, the degree of customer problem-solution and the degree of external collaboration are identified as the two dominant factors to describe the strategic innovation problem, and thus the innovation problem solving focus. As a result, on the basis of customer needs theory and transaction cost theory, the four generic situations are derived, and operationalised together with pre-project activities and the concept of methods. On the basis of the operationalised concepts, propositions about adequate method selection were derived, and further evaluated and illustrated by case study research. The thesis ends with the development of hypotheses about the framework and the value of appropriate method selection. On the basis of these hypotheses, requirements for appropriate method selection, in different organisational situations were developed. The central contribution to knowledge provided by this research is the approach to the innovation pre-project phase on the conceptual level in contrast to the existing approaches on an organisational or strategic level. By the development and application of the theoretical framework, research about methods can be conducted on a more general level and then be refined and taylored to specific organisational situations. Redundancies and contradictions from comparison of research conducted for specific situations can be explained, and further accumulation of knowledge in the field of preproject innovation activities is enabled. As a result, the developed mid-range theory allows a more comprehensive and structured approach to evaluate and understand the innovation pre-project phase compared to existing research in this topic.